SURG-08. 5-Aminolevulinic acid (5-ALA)-guided resection of pediatric brain tumors. (3rd June 2022) - Schwake, Michael; Bruns, Ann-Katrn; Müther, Michael; Stummer, Walter
Abstract: BACKGROUND: 5-Aminolevulinic acid (5-ALA)-guided resection of gliomas in adults enables better differentiation between tumor and normal brain, allowing a higher degree of resection, and improved patient outcomes. In recent years, several reports have emerged regarding the use of 5-ALA in other brain tumor entities, including pediatric brains tumors. Since gross total resection (GTR) of many brain tumors in children is crucial, the role of 5-ALA-guided resection requires elucidation. METHODS: A systematic literature review of EMBASE and MEDLINE/PubMed databases revealed 20 eligible publications encompassing 186 5-ALA-guided operations on pediatric brain tumors. To reduce bias, publications were revised independently by two authors. RESULTS: 5-ALA-guided resection enabled the surgeons to identify the tumor more easily and was considered helpful mainly in cases of glioblastoma (GBM, 21/27, 78%), anaplastic ependymoma WHO grade III (10/14, 71%), and anaplastic astrocytoma (4/6, 67%). In contrast, cases of pilocytic astrocytomas (PAs) and medulloblastomas 5-ALA-guided surgery did not show consistent fluorescent signals and 5-ALA was considered helpful only in 12% and 22% of cases, respectively. Accumulation of fluorescent porphyrins seems to depend on WHO tumor grading. In case fluorescence signal was considered helpful, it was associated to a greater degree of resection. One study showed an association between visible fluoresce signal and concentration of protopophyrin IX (PPIX) concentration. A threshold of 4μg/ml was required in order to visualize the fluorescence signal. The rate of adverse events related to 5-ALA was negligible, especially new postoperative sequelae. CONCLUSION: 5-ALA could play a role in resection of malignant, contrast enhancing, supratentorial pediatric brain tumors. At present, we are conducting a prospective phase I-II multicenter clinical trial to evaluate side effects and feasibility of 5-ALA guided surgery